IDENTIFIKASI NEED ASSESSMENT: STUDI AWAL MODEL PENGEMBANGAN BANK SOAL BERBASIS GURU DI PROVINSI DIY - Pujiati Suyata (Jurnal Kependidikan, 2010)
The study was aimed at identifying the necessity of developing teacher-based test item banks in the province of Yogyakarta. The identification of field conditions to become input for further studies contained: the definition of teacher-based test item banks, characteristics of teacher-based test kit, and equalization analyses of test item characteristics among different places. Using the survey design, the study collected data through questionnaires, interviews, and focus group discussion. The subjects included 42 teachers of physical sciences, mathematics, English and Indonesian, 5 school principals, and 5 office staff members. Data were analyzed quantitatively and qualitatively. Findings showed that (1) no item test bank existed in the province nor in the district; (2) analyses of test item characteristics were conducted by a small number of teachers (3) use of evaluation results for learning washback effects was not yet conducted. In relation to the existence of the teachers association and principals association and the carrying out of the final semester test unison, a model of test-item bank development can be developed through item test construction by the teachers association and principals association